Impact of an HIV-trained clinical pharmacist intervention on error rates of antiretroviral and opportunistic infection medications in the inpatient setting - Chiampas TD; Biagi MJ; Badowski ME. (Pharmacy Practice, 2019)
Background: Based on a retrospective study performed at our institution, 38% of inpatients living with human immunodeficiency virus (HIV) were found to have a medication error involving their anti-retroviral (ARV) and/or opportunistic infection (OI) prophylaxis medications. Objective: To determine the impact of a dedicated HIV-trained clinical pharmacist on the ARV and OI prophylaxis medication error rates at our institution. Methods: A prospective quality improvement project was conducted over a six month period to assess the impact of a dedicated HIV-trained clinical pharmacist on the ARV and OI prophylaxis medication error rates. IRB approval received. Results: There were 144 patients included in this analysis, who experienced a combined 76 medication errors. Compared to historical control study conducted at our institution, the percent of patients who experienced a medication error remained stable (38% vs. 39%, respectively) and the error rate per patient was similar (1.44 vs. 1.36, p=NS). The percent of medication errors that were corrected prior to discharge increased from 24% to 70% and the median time to error correction decreased from 42 hours to 11.5 hours (p<0.0001). Conclusions: Errors relating to ARV or OI prophylaxis medications remain frequent in inpatient people living with HIV/AIDS. After multiple interventions were implemented, ARV and OI prophylaxis medication errors were corrected faster and with greater frequency prior to discharge, however, similar rates of errors for patients existed. Dedicated HIV clinicians with adequate training and credentialing are necessary to manage this specialized disease state and to reduce the overall number of medication errors associated with HIV/AIDS.